Product Needs Planning For Distribution Fulfillment With Double Exponential Smoothing And Distribution Requirements Planning Methods: Perencanaan Kebutuhan Produk Untuk Pemenuhan Distribusi Dengan Metode Double Exponential Smoothing dan Distribution Requirements Planning - Natadiharja, Sebastian Arya; Wulandari, Indah Apriliana Sari; Sukmana, Tedjo; Cahyana, Atikha Sidhi (Procedia of Engineering and Life Science, 2023)
PT. KINI is a company engaged in the distribution of Indosat products. In the distribution process, there is often a shortage of stock for the Voucher type, and there is an excess stock for the SP type. The purpose of this research is to plan product needs before distribution, especially for products that often experience stock shortages. The application of the Double Exponential Smoothing forecasting method, and Distribution Requirement Planning are expected to overcome problems in the lack of fulfillment of product needs. The results of the research showed that the quantity of economical orders based on forecasting on V 3 in 1 products was 18,345 frequency of ordering 6 times, FI 1.5 GB of 11,715 frequency of ordering 4 times, FI 2.5 GB of 12,236 frequency of ordering 4 times, FI 5, 5 GB of 10,075 message frequencies 3 times, 3 GB FI of 11,874 message frequencies 4 times, and 9 GB FI of 6,566 message frequencies 2 times. The conclusions obtained from the development of the DES and DRP methods are the most economical order quantity, and the right time to order to overcome shortages in stock data voucher type products.